Beyond fandom: Outlander Facebook fan groups and the guardianship of an imagined Scotland. (1st March 2020) - Garrison, Stephanie
With the release of the novel Outlander (1991) by American author Diana Gabaldon and the subsequent television adaptation in 2014, Scotland has experienced an exponential rise in screen tourism which is being dubbed the 'Outlander effect'. While the steady influx of Outlander fans is mostly perceived as an economic boon, media outlets and heritage agencies have begun reporting damages to Scottish heritage sites due to increased Outlander-related tourism. The media coverage of these damages depicts the actions of 'rampaging', 'loutish', 'crack-pot', 'selfie-mad' Outlander fans which is proving to be a troubling colouration of Outlander fans in the media. This article examines the relationship between an online Outlander Facebook fan community called OutlandishUK and tourism to Scotland. Drawing from ethnographic and netnographic research, this article examines how online Facebook fan groups are embracing the role of being proactive online communities that engage fluidly with members of the media and regional interest groups to promote proper care of heritage sites in Scotland by the wider Outlander fandom. In contrast to the negative colouration of fans as vandals, the article suggests that it is through these collaborative efforts these fan groups are looking beyond fandom to act as guardians of Scottish heritage and facilitate regional tourism in Scotland.